Eksplorasi Pengaruh Live Shopping terhadap Minat Beli Konsumen dalam Berbelanja Online dengan Metode Systematic Literature Review - Irtiyah Izzaty Mindiasari; Diah Priharsari; Welly Purnomo (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2023)
Live Shopping is a new trend that combines e-commerce and social networking where the consumers who watch it can immediately buy with their smartphone just in one touch. Users who like to watch live shopping tend to have an interest in the products that are being offered in the live streaming. According to previous research, the live shopping strategy can increase user interest in buying products online regardless of distance and trading of goods. This phenomenon has been widely researched by experts before to explain what live shopping is, the technology that used to, or marketing strategies using live shopping, but there is not much literature that really leads to the emergence of buying interest in consumers through live shopping. For this reason, a Systematic Literature Review was conducted to review previous journals that discussed live shopping and purchase intention to determine the effect of using live shopping on consumer purchase intention in shopping online. The journal search process is carried out in several selection times and calculates Cohen's Kappa as a measure of the reliability of the journals found. The source of the journal search was carried out on ScienceDirect and the minimum year of the selected journal was 2011. The results obtained were 13 selected journals and after data extraction there were 51 factors that influence live shopping on purchase intention and 18 theories that can be used to identify the factors.